Thermodynamic analysis of a novel hybrid wind-solar-compressed air energy storage system. (15th June 2017) - Ji, Wei; Zhou, Yuan; Sun, Yu; Zhang, Wu; An, Baolin; Wang, Junjie
Highlights: We present a novel hybrid wind-solar-compressed air energy storage system. Wind and solar power are transformed into stable electric energy and hot water. The system output electric power is 8053 kWh with an exergy efficiency of 65.4%. Parametric sensitivity analysis is presented to optimize system performance. Abstract: Wind and solar power have embraced a strong development in recent years due to the energy crisis in China. However, owing to their nature of fluctuation and intermittency, some power grid management problems can be caused. Therefore a novel hybrid wind-solar-compressed air energy storage (WS-CAES) system was proposed to solve the problems. The WS-CAES system can store unstable wind and solar power for a stable output of electric energy and hot water. Also, combined with organic Rankin cycle (ORC), the cascade utilization of energy with different qualities was achieved in the WS-CAES system. Aiming to obtain the optimum performance, the analysis of energy, exergy and parametric sensitivity were all conducted for this system. Furthermore, exergy destruction ratio of each component in the WS-CAES system was presented. The results show that the electric energy storage efficiency, round trip efficiency and exergy efficiency can reach 87.7%, 61.2% and 65.4%, respectively. Meanwhile, the parameters analysis demonstrates that the increase of ambient temperature has a negative effect on the system performance, while the increase of turbine inlet temperature has a positive effect. However, when the air turbine inlet pressure varies, there is a tradeoff between the system performance and the energy storage density.